Analisis Kualitas Pelayanan dan Fasilitas Day-Spa di Medan - Shafira Ayu Syukrani; M. Rezki Setiawan; Ferdiana Shinta Triliasa; Dandi Nostiagi Rosta; Imam Fauzan Syahputra; Indra Kesuma Hadi; Muhammad Amin (RUAS (Review of Urbanism and Architectural Studies), 2020)
The purpose of this study is to find out the quality of services and Day-Spa facilities that correspond to user needs, especially Ubud Family Reflexology, De Spa, and Zengarden in Medan. In Medan City, day-spas are located are many located near shopping malls, elite settlements, office complex, and commercial areas. They are widely consumed by office executives, socialite mothers, college students, babies, and toddlers. In designing a spa building, it needs to observe and consider psychological users, especially consumers, it should be noted that facilities and privacy levels in the room are affecting consumer behavior. The research methods use interviewing, observing, and analyzing the document study. The results from this study indicate that day-spa buildings in Medan do not apply standard facilities and spa services.